Preparation method and application of in-situ polymerized high-thermal-conductivity gel polymer electrolyte
Through the preparation method of in-situ polymer electrolytes, the problems of lithium dendrites growth, poor safety performance, low interface compatibility and low ionic conductivity in lithium metal batteries are solved, and the high thermal conductivity and cyclic stability of the battery are achieved, which extends the battery life and reduces safety risks.
Patent Information
- Application Number
- CN202411801400.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
Li dendrites are easily grown on the surface of lithium negative electrodes in lithium metal batteries, with poor safety performance, poor compatibility between the electrolyte and electrode interface, and low ionic conductivity, resulting in a shortening of the battery's cycle life and an increase in safety risks.
Using the preparation method of in-situ polymerization of high thermal conductivity gel polymer electrolyte, the gel polymeric monomer is mixed with an organic solvent in a glove box filled with inert gas, added lithium salt and additives, and then added initiator to form a precursor solution, and left to stand at room temperature for 24-28 hours to form a gel polymer electrolyte. This method introduces a high thermal conductivity material h-BN to improve the thermal conductivity of the electrolyte.
It improves the comprehensive electrochemical performance of lithium metal batteries, enhances the safety and cycle stability of the battery at high temperatures, significantly improves the thermal conductivity and interface compatibility of the battery, extends the cycle life of the battery, and reduces safety risks.
Smart Images

Figure CN119725707A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a preparation method of an in-situ polymerized high thermal conductivity gel polymer electrolyte and application thereof. Background Art
[0002] Lithium metal batteries have great potential for application in many fields such as electric vehicles and portable devices in the future due to their high energy density and strong power tolerance. These characteristics enable lithium metal batteries to provide stronger power support and longer endurance for various devices, thus meeting the growing demand for efficient energy storage and supply in modern society.
[0003] At present, the electrolytes commonly used in lithium metal batteries mainly include organic liquid electrolytes, inorganic solid electrolytes and polymer electrolytes. In the organic liquid electrolyte system, lithium ions will be unevenly deposited during the charging and discharging process, which will cause uncontrollable lithium dendrite growth. The harm caused by the growth of lithium dendrites cannot be underestimated. The first is that the Coulomb efficiency of lithium metal batteries is reduced, that is, the ratio of the actual storage and release of the battery to the theoretical power is reduced, which seriously affects the energy utilization efficiency of the battery; secondly, the cycle life of the battery will be greatly shortened due to the continuous growth and accumulation of lithium dendrites and the destruction of the internal structure of the battery; the most serious is that lithium dendrites may pierce the diaphragm, causing the positive and negative electrodes of the battery to short-circuit, which will not only cause the battery to fail instantly, but also very likely to cause extremely serious safety problems such as thermal runaway. In addition, the thermodynamic instability, flammability and volatility of organic liquid electrolytes themselves further aggravate the safety risks of lithium metal batteries.
[0004] Compared with liquid lithium metal batteries, solid-state batteries are expected to be significantly improved in terms of safety performance. Among them, inorganic solid electrolytes have the advantage of good stability, but they face serious electrode interface problems. The poor interface compatibility between the electrolyte and the electrode leads to increased ion transfer resistance and triggers complex interface reactions, which have a serious impact on the overall performance of the battery. Moreover, the preparation process of inorganic solid electrolytes is not yet mature, and there is still a large gap from the actual large-scale application. Although polymer electrolytes have high flexibility and safety, their ionic conductivity is extremely low at room temperature. This defect seriously hinders the rapid transmission of lithium ions, making the battery charge and discharge rate slow under normal temperature working conditions and the power performance poor, which greatly limits its practical application. Summary of the invention
[0005] The present invention aims to provide a method for preparing an in-situ polymerized high thermal conductivity gel polymer electrolyte and its application, so as to solve the problems existing in the prior art, such as the easy growth of lithium dendrites on the surface of the lithium negative electrode, poor safety performance, poor compatibility between the electrolyte and the electrode interface, and low ion conductivity, thereby improving the comprehensive electrochemical performance of the battery; and having good thermal conductivity in a high temperature environment.
[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a high thermal conductivity gel polymer electrolyte by in-situ polymerization, comprising the following steps:
[0007] S1: In a glove box filled with inert gas, the polymerization monomer and the organic solvent are mixed uniformly at a volume ratio of (10-15):1 to obtain a mixed solution No. 1;
[0008] S2: dissolving a certain amount of lithium salt and additives in the mixed solution No. 1 in S1 to form a mixed solution No. 2;
[0009] S3: adding an initiator to the mixed solution No. 2 in S2 and mixing them evenly to obtain a precursor solution;
[0010] S4: Inject the precursor solution in S3 into the battery and let it stand at room temperature for 24-28 hours to obtain an in-situ polymerized high thermal conductivity gel polymer electrolyte.
[0011] Preferably, in S1, the polymerizable monomer is any one of 1,3-dioxane and 1,3-dioxolane; and the organic solvent is fluoroethylene carbonate.
[0012] Preferably, the concentration of fluoroethylene carbonate is 1-1.5 mol / L.
[0013] Preferably, in S2, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0014] Preferably, in S2, the additive is any one of hexagonal boron nitride and aluminum nitride.
[0015] Preferably, in S2, the mass of the additive is 15%-25% of the total mass of the polymerized monomers.
[0016] Preferably, in S2, the concentration of the lithium salt is 0.5-1 mol / L.
[0017] Preferably, in S3, the initiator is any one of trioxane (pentafluorophenyl) borane, aluminum trifluoromethanesulfonate and lithium hexafluorophosphate.
[0018] Preferably, the mass of the initiator is 1%-1.5% of the total mass of the polymerized monomers.
[0019] Compared with the prior art, the beneficial effects of this solution are:
[0020] (1) In this technical solution, in a glove box filled with inert gas, the polymerized monomers and organic solvents are mixed evenly in a certain volume ratio, the lithium salt and additives are dissolved in the mixed solution, the initiator is added to the mixed solution, and the mixture is mixed evenly to obtain a precursor solution, which is injected into the battery and left to stand at room temperature for 24-28 hours, so that the polymerized monomers undergo ring-opening polymerization in the battery under the action of the initiator to form a gel polymer electrolyte. Since the low-viscosity precursor solution has excellent fluidity and wettability, an integrated three-dimensional network of the entire battery is formed after in-situ polymerization, which effectively ensures the close contact between the electrolyte and the active particles; at the same time, the introduction of h-BN with a high thermal conductivity into the PDOL gel electrolyte greatly improves the thermal conductivity of the h-BN@PDOL gel electrolyte, which is conducive to the timely dissipation of the heat generated during the battery cycle and ensures the safe operation of the battery. The preparation method of this technical solution is simple and convenient, and can meet the requirements of large-scale production. At the same time, the large-scale production characteristics lay a solid foundation for its wide application. Large-scale production means that the market demand for h-BN@PDOL gel electrolyte can be met, whether in the field of electric vehicle batteries to improve battery performance and safety, meet the needs of long battery life and fast charging; or in the field of other electronic device batteries, such as smartphones, tablets, etc., to provide more stable and efficient energy support. Therefore, this method is conducive to the widespread application of h-BN@PDOL gel electrolyte in practice and promotes the development and progress of related industries.
[0021] (2) At 60°C, after 100 cycles, the LFP||h-BN@PDOL||Li battery assembled with h-BN@PDOL gel electrolyte had a discharge capacity of 134.2 mAh / g, a capacity retention rate of 87.7%, and a coulombic efficiency close to 100%. It can be seen that the introduction of h-BN not only stabilizes the interface between the electrolyte and the negative electrode, inhibits the occurrence of side reactions to a certain extent, but also inhibits the growth of lithium dendrites, and has faster heat dissipation during the cycle, which generally improves the electrochemical performance of the battery at high temperatures.
[0022] (3) This technical solution uses symmetrical cells and full cells to conduct in-depth research on the electrochemical properties, thermal conductivity and heat dissipation of h-BN@PDOL gel electrolyte in high temperature environments. The research results clearly show that h-BN@PDOL gel electrolyte exhibits excellent thermal conductivity and heat dissipation performance. In terms of thermal conductivity, it can efficiently transfer heat to ensure a more uniform heat distribution inside the battery and avoid local overheating. In terms of heat dissipation performance, in a high temperature environment, the electrolyte can quickly dissipate the heat generated during battery operation and maintain the battery in a suitable operating temperature range, thereby effectively ensuring the safe and stable operation of the battery.
[0023] At the same time, the h-BN@PDOL gel electrolyte also exhibits excellent cycle stability. During multiple charge and discharge cycles, its performance remains relatively stable, and it can continuously provide a reliable ion transmission channel for the battery to ensure the normal operation of the battery. It has a high ionic conductivity, which makes the migration of lithium ions in the electrolyte smoother and improves the charge and discharge efficiency of the battery. In addition, the electrolyte can effectively improve the interface stability, significantly improve the interface compatibility between the electrode and the electrolyte, and reduce the occurrence of side reactions at the interface. Through these combined advantages, the cycle life of lithium metal batteries is greatly improved, providing strong technical support for the long-term and stable use of lithium metal batteries, and further expanding its application potential in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A relationship diagram between temperature and thermal conductivity of 20% h-BN@PDOL, PDOL, 10% h-BN@PDOL, 30% h-BN@PDOL and 40% h-BN@PDOL gel electrolytes prepared in Example 1 and Comparative Examples 1-4 of the present invention;
[0025] Figure 2 At a current density of 1 mA / cm 2 , the deposition amount is 1mAh / cm 2 Under the conditions of , a curve chart of the cycle performance test of a symmetrical battery assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1, the 10% h-BN@PDOL gel electrolyte prepared in Comparative Example 2, and the 30% h-BN@PDOL gel electrolyte prepared in Comparative Example 3;
[0026] Figure 3 (a) Li||h-BN@PDOL||Li symmetric cell assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 at 0.1 mA / cm 2 , 0.1mAh / cm 2 Cyclic performance curve under the following conditions:
[0027] Figure 3 (b) Li||h-BN@PDOL||Li symmetric cell assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 at 0.5 mA / cm 2 , 0.5mAh / cm 2 Cyclic performance curve under the following conditions:
[0028] Figure 4(a) Impedance diagrams of a Li||h-BN@PDOL||Li symmetric battery assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 and a Li||PDOL||Li symmetric battery assembled with PDOL gel electrolyte prepared in Comparative Example 1;
[0029] Figure 4 (b) Electrochemical window diagram of the Li||h-BN@PDOL||SS symmetric battery assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1 and the Li||PDOL||SS symmetric battery assembled with the PDOL gel electrolyte prepared in Comparative Example 1;
[0030] Figure 4 (c) Ionic conductivity diagram of the Li||h-BN@PDOL||Li symmetric battery assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1 and the Li||PDOL||Li symmetric battery assembled with the PDOL gel electrolyte prepared in Comparative Example 1;
[0031] Figure 5 (a) The charge and discharge curves of the LFP||h-BN@PDOL||Li full cell assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1 and the LFP||PDOL||Li full cell assembled with the PDOL gel electrolyte prepared in Comparative Example 1 at a current density of 1C and the corresponding charge and discharge curves at different cycles;
[0032] Figure 5 (b) The charge and discharge curve of the LFP||PDOL||Li full cell assembled with the PDOL gel electrolyte prepared in Comparative Example 1 at a current density of 1C;
[0033] Figure 5 (c) The charge and discharge curve of the LFP||h-BN@PDOL||Li full cell assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1 at a current density of 1C;
[0034] Figure 5 (d) The charge and discharge curves of the LFP||h-BN@PDOL||Li full cell assembled with the 20% h-BN@PDOL gel electrolyte prepared in Example 1 and the LFP||PDOL||Li full cell assembled with the PDOL gel electrolyte prepared in Comparative Example 1 at a current density of 5C and the corresponding charge and discharge curves at different cycles;
[0035] Figure 5 (e) The charge and discharge curve of the LFP||PDOL||Li full cell assembled with the PDOL gel electrolyte prepared in Comparative Example 1 at a current density of 5C;
[0036] Figure 5(f) The charge and discharge curve of the LFP||h-BN@PDOL||Li full cell assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 at a current density of 5C;
[0037] Figure 6 (a) LFP||h-BN@PDOL||Li full cell assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 and LFP||PDOL||Li full cell assembled with PDOL gel electrolyte prepared in Comparative Example 1, at 60°C, current density of 1C and their corresponding charge and discharge curves at different cycles;
[0038] Figure 6 (b) The charge and discharge curves of the LFP||PDOL||Li full cell assembled with the PDOL gel electrolyte prepared in Comparative Example 1 at 60°C and a current density of 1C;
[0039] Figure 6 (c) The charge and discharge curves of the LFP||h-BN@PDOL||Li full cell assembled with 20% h-BN@PDOL gel electrolyte prepared in Example 1 at 60°C and a current density of 1C. DETAILED DESCRIPTION
[0040] The following is further described in detail through specific implementation methods:
[0041] Example 1
[0042] The method for preparing an in-situ polymerized high thermal conductivity gel polymer electrolyte comprises the following steps:
[0043] S1: In a glove box filled with inert gas, the polymerizable monomer and the organic solvent are uniformly mixed in a volume ratio of (10-15):1 to obtain a mixed solution No. 1, wherein the inert gas is any one of argon and helium, the organic solvent is fluoroethylene carbonate (FEC), and the concentration of fluoroethylene carbonate is 1-1.5 mol / L; the polymerizable monomer is any one of 1.3-dioxane and 1.3-dioxolane (DOL); in this embodiment, the inert gas is argon, the polymerizable monomer is 1.3-dioxolane (DOL), the concentration of 1.3-dioxolane (DOL) is 12.9 mol / L, the concentration of fluoroethylene carbonate is 1.25 mol / L, and the volume ratio of 1.3-dioxolane to fluoroethylene carbonate is 10:1, that is, 5 mL of 1.3-dioxolane and 0.5 mL of fluoroethylene carbonate are measured;
[0044] S2: dissolving a certain amount of lithium salt and additive in the mixed solution No. 1 in S1 to form a mixed solution No. 2, wherein the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the additive is any one of hexagonal boron nitride (h-BN) and aluminum nitride; the mass of the additive is 15%-25% of the total mass of the polymerized monomer, and the concentration of the lithium salt is 0.5-1 mol / L. In this embodiment, the additive is hexagonal boron nitride (h-BN), the mass of the additive is 20% of the total mass of the polymerized monomer, the mass of the lithium salt is 0.87 g, and the concentration of the lithium salt is 1 mol / L;
[0045] S3: adding an initiator to the mixed solution No. 2 in S2 and mixing them evenly to obtain a precursor solution, wherein the initiator is any one of trioxane (pentafluorophenyl) borane (TB), aluminum trifluoromethanesulfonate and lithium hexafluorophosphate, and the mass of the initiator is 1%-1.5% of the total mass of the polymerized monomers; in this embodiment, the initiator is trioxane (pentafluorophenyl) borane (TB), and the mass of the initiator is 1% of the total mass of the polymerized monomers;
[0046] S4: Inject the precursor solution in S3 into the battery and let it stand for 24-28 hours at room temperature to prepare an in-situ polymerized high thermal conductivity gel polymer electrolyte, which is recorded as 20% h-BN@PDOL gel electrolyte. In this embodiment, let it stand for 24 hours.
[0047] The prepared in-situ polymerized high thermal conductivity gel polymer electrolyte is applied in lithium metal batteries.
[0048] Comparative Example 1
[0049] Different from Example 1, in the method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte, in S2, no hexagonal boron nitride is added, that is, the addition amount of h-BN is 0, and the prepared in-situ polymerized high thermal conductivity gel polymer electrolyte is recorded as PDOL gel electrolyte.
[0050] Comparative Example 2
[0051] Different from Example 1, in the method for preparing an in-situ polymerized high thermal conductivity gel polymer electrolyte, in S2, the addition amount of hexagonal boron nitride accounts for 10% of the total mass of 1.3-dioxolane, and the prepared in-situ polymerized high thermal conductivity gel polymer electrolyte is recorded as 10% h-BN@PDOL gel electrolyte.
[0052] Comparative Example 3
[0053] Different from Example 1, in the method for preparing an in-situ polymerized high thermal conductivity gel polymer electrolyte, in S2, the added amount of hexagonal boron nitride accounts for 30% of the total mass of 1.3-dioxolane, and the prepared in-situ polymerized high thermal conductivity gel polymer electrolyte is recorded as 30% h-BN@PDOL gel electrolyte.
[0054] Comparative Example 4
[0055] Different from Example 1, in the method for preparing an in-situ polymerized high thermal conductivity gel polymer electrolyte, in S2, the added amount of hexagonal boron nitride accounts for 40% of the total mass of 1.3-dioxolane, and the prepared in-situ polymerized high thermal conductivity gel polymer electrolyte is recorded as 40% h-BN@PDOL gel electrolyte.
[0056] Testing the various properties of the in-situ polymerized high thermal conductivity gel polymer electrolytes prepared in Example 1 and Comparative Examples 1-4
[0057] (1) Testing the thermal conductivity of the in-situ polymerized high thermal conductivity gel polymer electrolytes prepared in Example 1 and Comparative Examples 1-4
[0058] Depend on Figure 1 It can be seen that the thermal conductivity of pure PDOL gel electrolyte is close to 0, and it has almost no thermal conductivity. When 10% h-BN is added, the thermal conductivity of 10% h-BN@PDOL gel electrolyte increases to 2.2W / m·K, and its thermal conductivity increases with the increase of temperature. As the amount of h-BN added gradually increases, the thermal conductivity of h-BN@PDOL gel electrolyte also gradually increases. When the content of h-BN is 40%, its thermal conductivity increases to 2.8W / m·K, but the change is not large. The selection of the appropriate content of h-BN still needs to be determined by electrochemical performance.
[0059] (2) Further study on the optimal content of h-BN in h-BN@PDOL gel electrolyte
[0060] Since the thermal conductivity of 40% h-BN@PDOL gel electrolyte is not much different from that of 20% h-BN@PDOL gel electrolyte, but the h-BN content in 40% h-BN@PDOL gel electrolyte is too high, only 10% h-BN@PDOL gel electrolyte, 20% h-BN@PDOL gel electrolyte and 30% h-BN@PDOL gel electrolyte are investigated below. The 20% h-BN@PDOL gel electrolyte prepared in Example 1, the 10% h-BN@PDOL gel electrolyte prepared in Comparative Example 2, and the 30% h-BN@PDOL gel electrolyte prepared in Comparative Example 3 are assembled into symmetrical batteries respectively. Example 1 is used as an example for explanation. The specific operation is as follows: lithium iron phosphate and metal lithium are used as the positive and negative electrode materials of the battery respectively, polypropylene diaphragm (PP, celgard 2400) is selected as the diaphragm material, and 20% h-BN@PDOL gel electrolyte is used as the electrolyte to assemble button cells. The symmetric battery assembly process of comparative examples 2 and 3 is the same as that of example 1, which will not be repeated here. Figure 2It can be seen that at room temperature, the current density is 1mA / cm 2 and deposition capacity 1 mAh / cm 2 In the cycling test, the 20% h-BN@PDOL gel electrolyte-based Li||Li symmetric battery showed a cycle life of nearly 680 hours, while the 10% h-BN@PDOL and 30% h-BN@PDOL gel electrolyte-based Li||Li symmetric batteries could only cycle for 580 hours and 600 hours, which may be due to the fact that the 10% h-BN content is too low to play the most effective role, and the 30% h-BN content is too high, blocking the ion transport and causing the electrochemical performance to decline. Based on this, 20% h-BN is the optimal content.
[0061] The current density was subsequently adjusted to 0.1 mA / cm 2 and 0.5mA / cm 2 , and the deposition capacity was adjusted to 0.1 mAh / cm 2 and 0.5mAh / cm 2 The long cycle test was carried out under Figure 3 As shown, the 20% h-BN@PDOL gel electrolyte-based Li||Li symmetric battery at 0.1 mA / cm 2 and 1mAh / cm 2 It can be cycled stably for 1800 hours at 0.5 mA / cm 2 and 0.5mAh / cm 2 The symmetrical battery can also be stably cycled for more than 1500 hours. In the late stage of cycling, the polarization voltage can still be stabilized within 100mV, indicating that 20% h-BN@PDOL gel electrolyte-based batteries can effectively improve the interface stability and increase the cycle life of lithium metal batteries.
[0062] (3) Study the effect of interfacial impedance on ion transport and battery cycling performance of h-BN@PDOL gel electrolyte
[0063] The 20% h-BN@PDOL gel electrolyte prepared in Example 1 was assembled into a 20% h-BN@PDOL gel electrolyte-based Li||Li symmetric battery, denoted as Li||h-BN@PDOL||Li symmetric battery; the PDOL gel electrolyte prepared in Comparative Example 1 was assembled into a PDOL gel electrolyte-based Li||Li symmetric battery, denoted as Li||PDOL||Li symmetric battery, and the interfacial impedances of the electrolytes of different systems were analyzed. Figure 4 (a) It can be seen that the interfacial impedance of the 20% h-BN@PDOL gel electrolyte is much smaller than that without h-BN, indicating that the gel polymer electrolyte prepared in the experiment has a stable SEI interface and excellent lithium ion transmission ability.
[0064] In order to further study the electrochemical stability of h-BN@PDOL gel electrolyte, the 20% h-BN@PDOL gel electrolyte prepared in Example 1 was assembled into a 20% h-BN@PDOL gel electrolyte-based Li||SS symmetric battery, denoted as Li||h-BN@PDOL||SS symmetric battery (wherein SS is a stainless steel sheet), and the PDOL gel electrolyte prepared in Comparative Example 1 was assembled into a PDOL gel electrolyte-based Li||SS symmetric battery, denoted as Li||PDOL||SS symmetric battery, and the batteries with different electrolyte systems were subjected to linear sweep voltammetry (LSV) tests, and the relevant curves are shown in FIG. Figure 4 As shown in (b), both 20% h-BN@PDOL gel electrolyte and PDOL gel electrolyte have an electrochemical window of 5.0 V, indicating that the presence of h-BN does not affect the antioxidant capacity of the electrolyte, and its good electrochemical stability is conducive to inhibiting the decomposition of the electrolyte and forming a stable electrode interface.
[0065] The ionic conductivity of different gel electrolytes was tested using the electrochemical impedance spectroscopy method, and the specific ionic conductivity of the solid electrolyte was calculated using the formula σ = L / R × S. Where σ is the ionic conductivity (S / cm), L is the thickness of the electrolyte (cm), R is the bulk resistance of the electrolyte (Ω), and S is the electrode area (cm 2 ). According to calculations, the conductivity of PDOL gel electrolyte is 2.73×10-4S / cm, while the conductivity of 20% h-BN@PDOL gel electrolyte is 7.14×10-4S / cm, which is about 3 times that of PDOL gel electrolyte. The reason for the improvement in conductivity may be that the presence of h-BN reduces the crystallinity of PDOL and promotes the Li + Rapid migration.
[0066] (4) Evaluation of the practicality of h-BN@PDOL gel electrolyte
[0067] The 20% h-BN@PDOL gel electrolyte prepared in Example 1 was assembled into a solid-state lithium battery coupled with a LiFePO4 (LFP) positive electrode, denoted as LFP||h-BN@PDOL||Li; the PDOL gel electrolyte prepared in Comparative Example 1 was assembled into a solid-state lithium battery coupled with a LiFePO4 (LFP) positive electrode, denoted as LFP||PDOL||Li; Example 1 is now taken as an example for illustration, and the specific operation is as follows: metallic lithium is used as the negative electrode, LiFePO4 (LFP) is used as the positive electrode active material of the battery, a polypropylene separator (PP, celgard 2400) is used as the separator material, and a 20% h-BN@PDOL gel electrolyte is used as the electrolyte to assemble a button cell. The full battery assembly process of Comparative Example 1 is the same as that of Example 1, and will not be repeated here. Figure 5(a) is a comparison of the discharge capacity and coulombic efficiency of LFP||PDOL||Li and LFP||h-BN@PDOL||Li full batteries at a current density of 1C. In the long-term cycle at a current density of 1C, the LFP||h-BN@PDOL||Li full battery cycle is stable for more than 100 cycles, with a first-cycle discharge capacity of 137.2mAh / g, a capacity retention rate of 89.0%, and a coulombic efficiency close to 100%. However, the first-cycle discharge capacity of the LFP||PDOL||Li full battery is only 60.8mAh / g. Figure 5 (b) and (c) are the charge and discharge curves of LFP||PDOL||Li and LFP||h-BN@PDOL||Li full batteries at a current density of 1C and different cycle numbers. It can be seen from the figure that the polarization voltage of the LFP||PDOL||Li battery gradually increases during the recycling process, resulting in capacity loss. Even if the current density is increased to 5C ( Figure 5 (d)), the LFP||h-BN@PDOL||Li full battery can also be stably cycled for 500 cycles with a capacity retention rate of 74%. However, the LFP||PDOL||Li full battery short-circuited after only 138 cycles. Figure 5 (e) and 5(f) are the charge and discharge curves of the corresponding full battery at 5C with different cycle numbers.
[0068] (5) Further study of the heat dissipation performance of h-BN@PDOL gel electrolyte
[0069] The 20% h-BN@PDOL gel electrolyte prepared in Example 1 was assembled into a solid-state lithium battery coupled with a LiFePO4 (LFP) positive electrode, denoted as LFP||h-BN@PDOL||Li; the PDOL gel electrolyte prepared in Comparative Example 1 was assembled into a solid-state lithium battery coupled with a LiFePO4 (LFP) positive electrode, denoted as LFP||PDOL||Li; and an electrochemical cycle test was performed at a high temperature of 60°C. Figure 6As shown in (a), the first discharge capacity of the LFP||h-BN@PDOL||Li battery at 60°C and a current density of 1C is 153.0mAh / g. After 100 cycles, the discharge capacity is 134.2mAh / g, the capacity retention rate is 87.7%, and the coulombic efficiency is close to 100%. The first discharge capacity of the LFP||PDOL||Li battery is 125.4mAh / g, and the capacity retention rate is only 78.2% after 100 cycles. In summary, after the introduction of h-BN, the interface between the electrolyte and the negative electrode is stabilized, the occurrence of side reactions is inhibited to a certain extent, and the heat dissipation is faster during the cycle, which generally improves the electrochemical performance of the battery at high temperature. The excellent electrochemical performance of the LFP||h-BN@PDOL||Li all-solid-state battery is mainly attributed to the following two points: ① Good interface wettability. Benefiting from the good wettability of the low-viscosity precursor solvent, an integrated three-dimensional network of the entire battery is formed after in-situ polymerization, ensuring close contact between the electrolyte and the active particles; ② The introduction of h-BN with high thermal conductivity into the PDOL gel electrolyte greatly improves the thermal conductivity of h-BN@PDOL, which is beneficial to dissipate the heat generated during the battery cycle in time and ensure the safe operation of the battery.
[0070] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a high thermal conductivity gel polymer electrolyte by in-situ polymerization, characterized in that: The following steps are involved: S1: In a glove box filled with inert gas, the polymerization monomer and the organic solvent are mixed uniformly at a volume ratio of (10-15):1 to obtain a mixed solution No. 1; S2: dissolving a certain amount of lithium salt and additives in the mixed solution No. 1 in S1 to form a mixed solution No. 2; S3: adding an initiator to the mixed solution No. 2 in S2 and mixing them evenly to obtain a precursor solution; S4: Inject the precursor solution in S3 into the battery and let it stand at room temperature for 24-28 hours to obtain an in-situ polymerized high thermal conductivity gel polymer electrolyte.
2. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 1, characterized in that: In S1, the polymerization monomer is any one of 1,3-dioxane and 1,3-dioxolane; and the organic solvent is fluoroethylene carbonate.
3. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 2, characterized in that: The concentration of fluoroethylene carbonate is 1-1.5 mol / L.
4. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 3, characterized in that: In S2, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
5. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 4, characterized in that: In S2, the additive is any one of hexagonal boron nitride and aluminum nitride.
6. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 5, characterized in that: In S2, the mass of the additive is 15%-25% of the total mass of the polymerized monomers.
7. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 4, characterized in that: In S2, the concentration of lithium salt is 0.5-1 mol / L.
8. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 7, characterized in that: In S3, the initiator is any one of trioxane (pentafluorophenyl) borane, aluminum trifluoromethanesulfonate and lithium hexafluorophosphate.
9. The method for preparing the in-situ polymerized high thermal conductivity gel polymer electrolyte according to claim 8, characterized in that: The mass of the initiator is 1%-1.5% of the total mass of the polymerization monomers.
10. Application of high thermal conductivity gel polymer electrolyte, characterized by: The in-situ polymerized high thermal conductivity gel polymer electrolyte prepared according to claims 1 to 9 is applied to lithium metal batteries.
Citation Information
Patent Citations
Polymer-based solid electrolyte with high room-temperature ionic conductance as well as preparation method and application thereof
CN112436188A
Solid-state battery interface optimization structure and preparation method
CN117525633A
Gel electrolytes for electrochemical devices, fabricating methods and applications of same
US20220209293A1
Cited By
High-safety lithium metal battery and preparation method thereof
CN120637564A